2018
DOI: 10.1016/j.appet.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Predicting preschool children's eating in the absence of hunger from maternal pressure to eat: A longitudinal study of low-income, Latina mothers

Abstract: Early work by Klesges et al. (1983, 1986) suggested that mothers who frequently prompt their children to eat have children at greater risk for obesity. This is consistent with the hypothesis that controlling feeding practices override children's responsiveness to their internal fullness cues, increasing the risk of overeating and obesity (e.g., Johnson & Birch, 1994). Subsequent cross-sectional research on pressure to eat, however, has been inconsistent. Most studies have shown that maternal self-reports of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…However Restriction was associated with greater eating of snack foods in the absence of hunger in 7 and 9 year‐olds, 9 and in 3–5 year‐olds who were given unlimited access to snack foods in a laboratory setting following a snack restriction period 27 . While two studies found no association between Pressure to eat and eating in the absence of hunger as assessed at school 19 and in a laboratory setting 23 where no parent was present, one study found that higher scores were associated with greater consumption of snack foods in the absence of hunger among preschool‐aged boys in a home setting where the mother was present 28 . Finally, in classic observation studies, greater observed maternal prompting behaviors have been positively correlated with child eating rate , 12 and the mere presence of mothers during a laboratory eating test with greater eating rate in children with obesity 29 .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…However Restriction was associated with greater eating of snack foods in the absence of hunger in 7 and 9 year‐olds, 9 and in 3–5 year‐olds who were given unlimited access to snack foods in a laboratory setting following a snack restriction period 27 . While two studies found no association between Pressure to eat and eating in the absence of hunger as assessed at school 19 and in a laboratory setting 23 where no parent was present, one study found that higher scores were associated with greater consumption of snack foods in the absence of hunger among preschool‐aged boys in a home setting where the mother was present 28 . Finally, in classic observation studies, greater observed maternal prompting behaviors have been positively correlated with child eating rate , 12 and the mere presence of mothers during a laboratory eating test with greater eating rate in children with obesity 29 .…”
Section: Introductionmentioning
confidence: 92%
“…Birch and Deysher performed the first study of caloric compensation in young children 21 . Eating in the absence of hunger, a behavioral test first applied in children by Birch and team, assesses intake of palatable snack foods when given simultaneous access to desirable play activities shortly after eating to satiety, thus giving an indication of the extent to which external cues drive eating in the absence of physiologic hunger 9,22,23 . Eating rate is considered an additional indicator of satiety sensitivity and appetite avidity, with slower eating and deceleration through the meal thought to indicate a stronger response to internal satiety signals, and faster eating rate thought to indicate greater motivation to eat 24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research is needed on parenting behaviors that shape child development through multiple mechanisms, including parent-child attachment relationships to develop trust, executive function skills (eg, paying attention, maintaining focus, planning), 69,70 and emotional regulation (eg, calming down when upset). 71 Parental behaviors also shape earlyemerging child health behaviors, including sleep habits, both duration and timing 72 ; engagement in physical and sedentary activity 73 ; media use 74,75 ; and eating behaviors 76,77 (eg, consumption of fruits and vegetables or sugar-sweetened beverages). 78,79 Little is known about the impact of sleep and sleep disorders on central cardiovascular control.…”
Section: Parenting Interventionsmentioning
confidence: 99%
“…Health promotion, from the perspective of behavioral sciences implies having a correct perception of internal locus of control and self-efficacy, [11][12][13][14][15][16] as well as parental styles for establishing healthy habits. [16][17][18][19] These elements must be developed in the primary caregivers for the establishment of habits and prioritization of the healthy nutritional status of the children; they should be included in the educational interventions for the achievement of the parental competence for correct nourishing (PCCN). [16-18, 20, 21] Studies have found that increasing the perception of self-efficacy and development of parenting skills has a positive effect on nutritional recovery.…”
Section: Introductionmentioning
confidence: 99%